Analisis Keterampilan Futsal Mahasiswa Penjas FKIP Universitas PGRI Palembang - M. Taheri Akhbar; Agung Mahendra; I Made Andika Bayu (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
The purpose of this study was to determine students' futsal skills. The research method used is descriptive research. The research population was 160 students who took part in the futsal course, while the sample comprised 60 people. The data collected in this study used a Futsal skill test instrument. Data analysis used the percentage formula. The results showed that the futsal skills of physical education students were included in the Enough category. It can be seen from the tests that have been carried out with the results of 60 students as much as 50% or 30 students having sufficient skills. In conclusion, the futsal skills of PGRI Palembang University students are in the Enough category Keywords: Futsal Skills, students